PENGARUH PEMBENTUKAN CIVIC SKILLS TERHADAP TINGKAT ASPIRASI PEMILIH PEMULA DI SMA AL-KAUTSAR KOTA BANDAR LAMPUNG - Kesuma, Tubagus Ali Rachman Puja (Lentera: Jurnal Ilmiah Kependidikan, 2014)
Political education, especially in the concept of political culture for citizens who become first-time voters is a shared responsibility. In the implementation of democracy in Indonesia, particularly citizen voters should have the skills of citizenship is good to be able to channel their aspirations well.The purpose of this study was to clarify the effect is the formation of civic skills to the level of the political aspirations of a class XI student voters at Al-Kautsar senior high School in the city of Bandar Lampung. Methods This was a descriptive correlational study, this sample is a class XI student who has become a first-time voters in Al-Kautsar senior high School in Bandar Lampung, amounting to 68 people, the data collection techniques used is to test and questionnaire data processing is then performed through the analysis of SPSS statistical version of 17:00.Civic Skills affect the level of the political aspirations of the students, It is based on the calculation of the path coefficient Ï> 0 is obtained Ï2 = 0.703 with a significance above 0.485 and the significance level Î± = 0.05 level real thus significantly influential variables.